Obfuscation and Diversification for Securing Cloud Computing - Shohreh Hosseinzadeh; Samuel Laurén; Sampsa Rauti; Sami Hyrynsalmi; Mauro Conti; Ville Leppänen (My University, 2022)
The evolution of cloud computing and advancement of its services has motivated the organizations and enterprises to move towards the cloud, in order to provide their services to their customers, with greater ease and higher efficiency. Utilizing the cloud-based services, on one hand has brought along numerous compelling benefits and, on the other hand, has raised concerns regarding the security and privacy of the data on the cloud, which is still an ongoing challenge. In this regard, there has been a large body of research on improving the security and privacy in cloud computing. In this chapter, we first study the status of security and privacy in cloud computing. Then among all the existing security techniques, we narrow our focus on obfuscation and diversification techniques. We present the state-of-the-art review in this field of study, how these two techniques have been used in cloud computing to improve security. Finally, we propose an approach that uses these two techniques with the aim of improving the security in cloud computing environment and preserve the privacy of its users.
Enterprise Security: Second International Workshop, ES 2015, Vancouver, BC, Canada, November 30 – December 3, 2015, Revised Selected Papers